2010
DOI: 10.1111/j.1755-3768.2008.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Oculometry findings in high myopia at adult age: considerations based on oculometric follow‐up data over 28 years in a cohort‐based Danish high‐myopia series

Abstract: ABSTRACT.Purpose: To present and discuss oculometry data in a series of adults with high myopia followed between the ages of 26 and 54 years. Emphasis is on axial length (AL) findings and corneal curvature radius (Crad).Methods: Thirty-four out of the 39 individuals recruited as teenagers from a Copenhagen 1948 birth cohort with myopia of at least 6 D have had current follow-up exams, to include AL measurements (by ultrasound, 1974-2002; the latter year also with the Zeiss IOLMaster) and keratometry. The cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…A longitudinal study in highly myopic eyes in adults reported an increase in the axial length [5]. In addition, Saka et al studied the medical records of 184 eyes of 101 high myopia patients with refractive errors of −6 D or more or with axial lengths of 26.5 mm or more and reported a significant increase of the axial length from 28.6 mm to 29.4 mm over the mean follow-up period of 8.2 years [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A longitudinal study in highly myopic eyes in adults reported an increase in the axial length [5]. In addition, Saka et al studied the medical records of 184 eyes of 101 high myopia patients with refractive errors of −6 D or more or with axial lengths of 26.5 mm or more and reported a significant increase of the axial length from 28.6 mm to 29.4 mm over the mean follow-up period of 8.2 years [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent longitudinal study by He et al, slight increase of the axial length in adults (mean refractive error, −0.44 ± 2.21 diopters) was reported [4]. Conversely, an increase in the axial length in adults with highly myopic eyes is common and has been previously shown in longitudinal studies [57]. However, to the best of our knowledge, there have been no studies directly comparing the increase in the axial length in adults with non-highly myopic eyes or highly myopic eyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work should be done to improve the PPV, such as including more risk factors in the prediction, i.e., history of myopic parents [24,25], environmental factors such as outdoor activity time [26,27], near work time, [28,29] and optical biometry. Further follow-up to determine progression rates may also improve predictive power[30]. One of our future directions is to incorporate these potential risk factors into our prediction method.…”
Section: Discussionmentioning
confidence: 99%
“…Highly significant correlation (p<0.001) was established between the two parameters. 38 Park et al came to the conclusion that shorter eyes i.e. eyes with increased corneal curvature show hyperopic shift while longer eyes i.e., eyes with decreased corneal curvature show myopic shift.…”
Section: Discussionmentioning
confidence: 99%